Assessing impacts of climate change and human activities on the abnormal correlation between actual evaporation and atmospheric evaporation demands in southeastern China. (May 2020) - Bai, Hua; Lu, Xianghui; Yang, Xiaoxiao; Huang, Jianchu; Mu, Xingmin; Zhao, Guangju; Gui, Faliang; Yue, Chao
Highlights: Abnormal correlation was verified between the actual evaporation ( AE ) and evaporation demands ( ED ) in the humid region. Penman and Budyko equations were combined to assess the integrated response chain from a changing environment to AE . The compensation function of afforestation was highlighted for the decrease in AE against the impact of decreasing ED . Transformation mechanism of the Penman into Bouchet hypotheses is investigated in the regional water-energy balance. Abstract: Generally, atmospheric evaporation demand ( AED ) shows a positive correlation with actual evaporation ( AE ) in the Yangtze River basin. In order to explore whether and why abnormal correlation exits in its five sub-basins, the temporal changes between AED and AE were compared, and then the impacts of climate change and human activities on abnormal correlations were assessed using the sensitivity method of Penman equation and the decomposition method of Budyko equation. The results indicated: (1) Pan evaporation and potential evaporation (indicators of AED ) decreased at rates of up to -0.04 and -0.06 mm d −1 decade −1, respectively. In contrast, the water budget-derived evaporation (an indicator of AE ) increased at the rate of 0.09 mm d −1 decade −1 in the Fuhe River basin and remained stable in other basins. Abnormal correlations (nonpositive correlations) were observed. (2) Decreasing net radiation and wind speed were major climate factors resulting in simultaneous temporal decreases in AED and AE . In contrast, afforestation was a major human factor leading to an increase in annual AE of 78 mm, but had no effect on AED . Afforestation was the primary driving force of the abnormal correlation. These results could provide water-energy guidance for urban climate change mitigation and flood/drought disaster management.